Comparison and Economic Feasibility Study of The Productivity of Five Varieties of Barley (Hordeum vulgare L.) - Ahmad, Mahmod Karem (Kurdistan Journal of Applied Research, 2018)
In general, economic and agricultural policy of the successive Iraqi governments was not toward agricultural development and achieve food security, whether for humans or animals, for dependence on exports of oil to import country’s food needs in a difficult currency, which cost the state budget amounts. Scientific and technological underdevelopment, lack of feasibility studies, economic performance,customs, social traditions, religious beliefs and neglect of the farmer caused a lack of interest in the cultivation of barley and its selection of high quality and quantity varieties of grains,straw,land, storage, and marketing operations.The study was conducted to assess the economic feasibility of the productivity of the five Asian barley varieties (Hordeum vulgare L.), (Arivat, Norma ,Iba99 ,NS313 andBip999) for grain and straw yield in Bakrajo area during the winter season of (2015 -2016). The results showed that grain and straw yield parameters were significantly varied according to varieties. Significant increase in grain yield (2720kg/ha), hay yield (3643kg/ha), grain and hay cost (736.180)1000ID/ha, hay revenue (582.880) 1000ID/ha, grain revenue (1019.997)1000ID/ha, profit (866.697)1000ID/ha, seed product (27.200) kg and 1000ID income (2.221) were recorded for NS313 and Bip999 varieties, while the number of grains / spike (44.133) and plant length (89.433) cm was recorded for Iba99 variety.